PENGARUH PEMBERIAN PUPUK NPK 15:15:15 TERHADAP PERTUMBUHAN TANAMAN SELASIH (Ocimum basilicum), MINT (Mentha spp) DAN SAMBUNG NYAWA (Gynura procumbens) - S, Tirta Salim.; Tarigan, Dafni Mawar; M.R, Razean Haireen, (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2025)
Basil (Ocimum basilicum), mint (Mentha spp.), and sambung nyawa (Gynura procumbens) are herbal plants with various benefits, both for culinary and medicinal purposes. Basil is known for its distinctive aroma and is often used in cooking and traditional medicine due to its essential oil content, which has antioxidant and anti-inflammatory properties. Mint, with its refreshing taste and aroma, is widely used in beverages, food, and medicines, especially for relieving digestive disorders. Meanwhile, sambung nyawa is a medicinal plant believed to help lower high blood pressure, improve immune function, and possess antioxidant properties. These three plants have great potential in the fields of agriculture and health. This study aims to examine the effect of NPK 15:15:15 fertilizer on the growth of three plant species: Basil (Ocimum basilicum), Mint (Mentha spp.), and Sambung Nyawa (Gynura procumbens). The research used a Randomized Block Design (RBD) with two treatments: N0 (control): no fertilizer application, and N1: NPK 15:15:15 fertilizer applied at a dose of 1.5 grams per plant. Parameters observed included plant height, number of leaves, canopy width, and chlorophyll content. The results showed that Basil (Ocimum basilicum) responded most significantly to the NPK 15:15:15 fertilizer compared to Mint (Mentha spp.) and Sambung Nyawa (Gynura procumbens). Basil showed significant improvement in all observed parameters, especially between 10-15 days after application (DAA). These results indicate that the application of NPK 15:15:15 has the potential to enhance the growth efficiency of Basil compared to the other two plants.